Carbohydrate Analysis and Acceptability Test of Purple Sweet Potato Pudding with Palm Sugar as a Healthy Snack Alternative for Teenagers - Nadia Nomaneci; Aminah Toaha; Astri Ayu Novaria; Yulian Andriyani (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
One of the problems that occurs in teenagers is obesity. One way to overcome the problem of obesity in teenagers is to consume healthy and nutritious food. The aim of this research was to determine the sensory evaluation and nutritional content (carbohydrates) of pudding with the addition of purple sweet potato. This research used a Completely Randomized Design (CRD) with three formulations and four repetitions. The three formulations used in making pudding with the addition of purple sweet potato have the formulations (85 grams), (80 grams) and (75 grams). Laboratory tests are carried out to determine nutritional content (carbohydrates). The results of this research show that the best purple sweet potato pudding with palm sugar is the addition of 85 grams of purple sweet potato which has a nutritional content (carbohydrate) of 12.94%.